Discovery, Synthesis, and Optimization of Diarylisoxazole‐3‐carboxamides as Potent Inhibitors of the Mitochondrial Permeability Transition Pore. Issue 10 (18th August 2015) - Roy, Sudeshna; Šileikytė, Justina; Schiavone, Marco; Neuenswander, Benjamin; Argenton, Francesco; Aubé, Jeffrey; Hedrick, Michael P.; Chung, Thomas D. Y.; Forte, Michael A.; Bernardi, Paolo; Schoenen, Frank J.
Abstract The mitochondrial permeability transition pore (mtPTP) is a Ca2+‐requiring mega‐channel which, under pathological conditions, leads to the deregulated release of Ca2+ and mitochondrial dysfunction, ultimately resulting in cell death. Although the mtPTP is a potential therapeutic target for many human pathologies, its potential as a drug target is currently unrealized. Herein we describe an optimization effort initiated around hit 1, 5‐(3‐hydroxyphenyl)‐N‐(3, 4, 5‐trimethoxyphenyl)isoxazole‐3‐carboxamide, which was found to possess promising inhibitory activity against mitochondrial swelling (EC50<0.39 μM) and showed no interference on the inner mitochondrial membrane potential (rhodamine 123 uptake EC50>100 μM). This enabled the construction of a series of picomolar mtPTP inhibitors that also potently increase the calcium retention capacity of the mitochondria. Finally, the therapeutic potential and in vivo efficacy of one of the most potent analogues, N‐(3‐chloro‐2‐methylphenyl)‐5‐(4‐fluoro‐3‐hydroxyphenyl)isoxazole‐3‐carboxamide (60), was validated in a biologically relevant zebrafish model of collagen VI congenital muscular dystrophies.